(untitled) (Oxford, UK, 1998)
"Reward" is a multi-level course designed to take students from their first introduction to English up to a fully proficient use of the language.
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Giáo trình dành cho người nước ngoài